2015
DOI: 10.1007/s10865-015-9662-1
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality is associated with better prostate cancer treatment decision making experiences

Abstract: This study examined whether spiritual beliefs are associated with greater decision-making satisfaction, lower decisional conflict and decision-making difficulty with the decision-making process in newly diagnosed men with prostate cancer. Participants were 1114 men diagnosed with localized prostate cancer who had recently made their treatment decision, but had not yet been treated. We used multivariable linear regression to analyze relationships between spirituality and decision-making satisfaction, decisional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 44 publications
5
19
0
2
Order By: Relevance
“…Individuals from different racial/ethnic groups or cultures may have religious or spiritual belief systems that contribute to their medical care seeking. (33, 4041), as we have demonstrated among patients with colorectal cancer (Figure 2) and breast cancer (Figure 3) (27, 37). In both studies, patients of minority race/ethnic background were much more likely to endorse the role of spirituality in care seeking than their white counterparts.…”
Section: The Role Of the Patient: Drawing On A Conceptual Frameworsupporting
confidence: 57%
“…Individuals from different racial/ethnic groups or cultures may have religious or spiritual belief systems that contribute to their medical care seeking. (33, 4041), as we have demonstrated among patients with colorectal cancer (Figure 2) and breast cancer (Figure 3) (27, 37). In both studies, patients of minority race/ethnic background were much more likely to endorse the role of spirituality in care seeking than their white counterparts.…”
Section: The Role Of the Patient: Drawing On A Conceptual Frameworsupporting
confidence: 57%
“…Two reports based on a sample of a LPC patient cohort found that increased spirituality was associated with greater decisional satisfaction, less decisional conflict, less decision-making difficulty, and less decisional regret [7, 8]. In addition, increased spirituality was shown to be associated with increased physical and mental health of men with prostate cancer, including improvement in emotional well-being and decrease in symptom distress and anxiety [38].…”
Section: Discussionmentioning
confidence: 99%
“…Since mortality is essentially the same for each treatment [4], experts recommend that treatment choice should be responsive to patient preferences [5]. These personal preferences have been shown to be shaped by a patient's own beliefs, personality traits [68], and the people that he interacts with during the decision-making process [7, 920], though many of these studies were performed in majority white populations. Understanding how men's personality traits and social influences impact the treatment decision-making process in a diverse population is important for physicians and other healthcare professionals to provide the best support possible for individual patients as they choose the best treatment for their unique circumstances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporando as correlações existenciais, religiosas e espirituais da Antropologia Filosófica (evolução das espécies e antropogênese; homem e Divindade; conduta ética-moral e essência espiritual; evolução espiritual e experiências de vida, dentre outras) [5][6][7] , a Antropologia Médica Vitalista também traz subsídios ao entendimento da influência das dimensões não materiais, espirituais e religiosas na etiopatogenia das doenças e nas práticas de promoção à saúde 57 , abordagem que vem assumindo importância crescente em relação ao enfrentamento, prognóstico, prevenção e tratamento de inúmeros distúrbios orgânicos [58][59][60][61][62][63][64][65][66][67][68][69][70][71] . Por valorizar esses aspectos espirituais e religiosos da individualidade no direcionamento da atenção clínica, a Associação Psiquiátrica Americana incluiu no Manual Diagnóstico e Estatístico de Transtornos Mentais (DSM-IV.…”
Section: Conclusõesunclassified